Mapping the Research Landscape: A Bibliometric Analysis of Innovative Work Behavior and Leadership Trends - Jadmiko, Purbo; Pratama, Putra; Huddin, Muhammad Nurhaula (JMB : Jurnal Manajemen dan Bisnis, 2025)
This study explores research trends and thematic patterns at the intersection of Innovative Work Behavior (IWB) and leadership through a bibliometric analysis using the Scopus database. The analysis includes 427 publications from 2019 to 2024. The bibliometric analysis was conducted using VOSviewer, a tool widely recognized for visualizing bibliometric networks. The software facilitated the identification of co-occurrence patterns, and thematic clusters. Keyword co-occurrence analysis revealed dominant themes such as "Innovative Work Behavior," "Transformational Leadership," and "Knowledge Sharing," while citation analysis identified influential authors and foundational works in the field. Cluster analysis highlighted interconnections between leadership styles, knowledge sharing, psychological safety, and organizational commitment, providing actionable insights into research gaps and emerging trends. Future research should explore Digital Leadership as a catalyst for innovation in hybrid work environments and Inclusive Leadership to enhance team-based innovation through psychological safety and diversity. Studies should also consider contextual factors such as cultural and sectoral differences, particularly in public and higher education institutions, to address the dynamic demands of modern organizations